PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PADA RETURN SAHAM - Firdausi, Fitria; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of external and internal factors to the stock return. The internalfactor is proxy by Return on Assets (ROA), Debt to Equity Ratio (DER), Earnings per Share (EPS), OperatingCash Flow (OCF) whereas the external factor is proxy by inflation and interest rate through the annual financialstatement which has been prepared by property and real estate companies which are listed in Indonesia StockExchange and the monthly report of Bank Indonesia.The samples are property and real estate companies whichare listed in Indonesia Stock Exchange by using purposive sampling method. The observation period is in 2011-2015 periods. The analysis method has been carried out by using multiple linear regressions analysis. The resultof the research shows that: (a) the ROA does not give any influence to the stock return, (b) the DER does giveany influence to the stock return, (c) the EPS give positive influence to the stock return, it means when earningsper share is getting high, (d) the OCF does not give any influence to the stock return, (e) the inflation givepositive influence to the stock return, (f) the interest rate give negative influence to the stock return.Keywords: Financial ratio, operating cash flow, inflation, interest rate, stock return